Social isolation during the COVID-19 pandemic increases the indicator of sarcopenia and sedentary behavior in Brazilians older adults - Oliveira, Daniel Vicentini de (2023)
Objective: to compare whether the indicative of sarcopenia and sedentary behavior increased during social isolation due to the COVID-19 pandemic in elderly Brazilians. Methods: Cross-sectional study conducted with 98 elderly people of both sexes, 64 men and 34 women from southern and southeastern Brazil, and who were in total or partial social isolation due to the COVID-19 pandemic (June to July 2020). The SARC-F and the International Physical Activity Questionnaire (IPAQ), short version, were used. The collection of quantitative data took place through an online form provided by Survey Monkey. Data were analyzed using the Kolmogorov-Smirnov, Levene, independent and dependent t tests, and Spearman's coefficient. Significance was adopted when p < 0.05. Results: women (p = 0.047) and the elderly who did not exercise (p = 0.001) had more time sitting after the onset of the pandemic. Younger elderly (p = 0.002) and those who reported having been exercising before social isolation (p = 0.006) had lower scores indicative of sarcopenia during the pandemic. The elderly showed an increase in sarcopenia indicatives (p = 0.050) and in sedentary behavior (p = 0.001) during the period of social isolation. Conclusion: the period of social isolation due to the COVID-19 pandemic caused an increase in the indicative of sarcopenia and in the sedentary behavior of the elderly.